Outcomes of Arthroscopic Microfracture Technique with Platelet-Rich Plasma (PRP) Injections in the Treatment of chondral ulcers of the knee joint - Ahmed Sayed Ahmed El Shamy, Mohamed Ramadan El-Fishawy, Usama Gaber Abdalla (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Normal hyaline cartilage regeneration is not possible in articular cartilage. In contrast, the conversion of mesenchymal tissue to fibrocartilage results in a reduced proteoglycan content relative to hyaline cartilage. Furthermore, due to its low resilience & inadequate stress response, fibrocartilage can be further degraded when subjected to joint trauma. Deterioration of articular cartilage's responsiveness to repeated stresses may result in a decline in the patient's performance, subsequently leading to chondropenia &eventually osteoarthritis.Objective: To evaluate the effectiveness of platelet-rich plasma (PRP) injections followed by arthroscopic microfracture for therapy of chondral ulcers of the knee joint.Patients & Methods: Twenty cases with knee problems were investigated, inspected, & scoped for their lesions. Their age range was 20–50 years. Patients were treated with arthroscopic microfractures plus platelet-rich plasma (PRP).Results: Twenty patients underwent arthroscopic microfracture in conjunction with PRP; fourteen cases reported improvement postoperatively, and six patients showed further improvement. Due to the inadequate resistance of fibrocartilage to compressive loads and the resulting fissuring and fragmentation, the long-term outcomes are less than promising.Conclusion: Arthroscopic microfracture followed by PRP injection has a great role in enhancing the healing of chondral lesions in short-term follow-up.